Popularisation of non-custodial penalties for inmates 60+. Reference to fragments of own research results - Katarzyna Gucwa-Porębska (Edukacja Ustawiczna Dorosłych)
Referring to the evolution of individual systems, it can be clearly noticed that along with the progress and development of civilization, the essence of probation interactions in the reintegration process is emphasized. Along with the development and dissemination of noncustodial penalties, the professionalization of activities in the area of the application of such penalties is more frequent. One of the forms of non-custodial penalties is electronic supervision system. The aim of this article is to present the main assumptions of ESS and its application in working with inmates 60+. The forms of support provided under electronic supervision and opinions on serving a sentence in ESS will be presented.